The Complexity of Contemporary Citizenship: A Typology of Citizenship Orientations Among Norwegian Digital Natives - Elizabeth Solverson; Stefan Geiß; Melanie Magin (Social Media + Society)
Democratic citizenship is continuously evolving, shaped by changing political, social, and media contexts. Digital natives—those who have come of age in environments where digital technologies are embedded in everyday life—have experienced citizenship in markedly different ways than previous generations. While the internet has broadened the repertoire of participatory behaviors, existing research has struggled to capture the complexity of contemporary citizenship. Drawing on deliberative systems theory and a triadic framework of citizenship—examining normative expectations, behaviors, and attitudes—this study develops a nuanced exploration of citizenship orientations. Using an innovative questionnaire and latent profile analysis of survey data from Norwegian digital natives (aged 18–40), we identify seven distinct citizenship types that reveal the multidimensional nature of contemporary citizenship. Our research moves beyond binary distinctions between active and passive citizenship, emphasizing the importance of both expressive and receptive behaviors across online and offline contexts. By highlighting the diverse roles citizens play in sustaining democratic processes, we offer new insights into citizenship in the digital age, demonstrating how different citizens contribute to the democratic system through varied and interdependent forms of engagement.